International retail firm acceptance: Beware of the flattery - Buame, S.C.K.; Acheampong, G. (International Journal of Business and Globalisation, 2015)
The study explored the effectiveness of ingratiation theory methods in achieving acceptance within the institutional contexts of emerging markets. The study reviewed literature on ingratiation theory, retail internationalisation and institutional to develop a conceptual model for testing. Data was collected using a systematic sampling procedure from Ghana using structured questionnaires and analysed by means of factor and regression analysis. The study found that ingratiation methods are not effective in overcoming institutional pressures in retailing sector in developing countries. Thus international retail firms should be careful in adopting these methods. This study contributes to internationalisation literature among retail firms in the developing and emerging economies by cautioning firms on the use of ingratiation theory methods. Copyright © 2015 Inderscience Enterprises Ltd.
Keywords: Ghana; Ingratiation; Institutional theory; Internationalisation; Legitimacy; Retailing